Clinical investigation of a daily disposable silicone hydrogel contact lens: stenofilcon A - Sapkota, Kishor (2016)
Purpose: The aim of this study was to investigate the effect of Stenofilcon A lens wear on conjunctival cytology, corneal biomechanical properties and conjunctival and corneal physiology. Methods: This was a longitudinal clinical case-control study conducted in University of Minho, Portugal. Fifteen neophyte subjects were fitted with a stenofilcon A lens in one eye and a comfilcon A in the other control eye. Impression cytology was performed on the superior bulbar conjunctiva. Goblet cell density (GCD) and epithelial cell morphology were studied with a light microscope. Ocular response analyzer was used to measure corneal resistance factor (CRF) and corneal hysteresis (CH). Ocular surface physiology (conjunctival limbal and bulbar redness, conjunctival and corneal staining) were examined with a slit lamp and graded according to Efron’s grading system. All of these tests were performed during baseline visit and after three months of lens wear. Results: The mean age of the subjects was 23.60±2.49 years and 73% were female. After three months, there was a significant decrease in CRF (p=0.008), but there was no change in CH (P=0.460). Cytological findings showed no change in GCD and epithelial cell metaplasia (p>0.05). There was an increase in corneal staining (p=0.001) but there was no change in bulbar redness, limbal redness and conjunctival staining (p>0.05). No significant difference was observed in changes between study eyes and the control eyes with comfilcon A lens wear (p>0.05). Conclusion: Stenofilcon A lens wear decreased CRF, but there was no change on conjunctival cytology and corneal and conjunctival physiology. Stenofilcon A lens affected the ocular surface similar with comfilcon A lens.